3D Spatial Combination of CN Vacancy‐Mediated NiFe‐PBA with N‐Doped Carbon Nanofibers Network Toward Free‐Standing Bifunctional Electrode for Zn–Air Batteries. Issue 11 (22nd February 2022) - Lai, Chenglong; Li, Haomiao; Sheng, Yi; Zhou, Min; Wang, Wei; Gong, Mingxing; Wang, Kangli; Jiang, Kai
Abstract: Constructing flexible free‐standing electrodes with efficient bifunctional performance is significant for improving the performance of flexible Zinc–air batteries. Herein, a flexible free‐standing bifunctional electrode (N2 ‐NiFe‐PBA/NCF/CC‐60) is constructed by the 3D spatial combination of CN vacancy‐mediated NiFe Prussian Blue Analogue (NiFe‐PBA) and N‐doped carbon nanofibers (NCF) rooted on carbon cloth (CC). The in situ formed CN vacancies by N2 ‐plasma activation tune the local coordination environment and electronic structure of Ni‐Fe active sites in NiFe‐PBA, thus improving the oxygen evolution reaction (OER) catalytic intrinsic activity, and restraining the loss of Fe element during OER process. The combination of NiFe‐PBA and NCF presents a 3D interworking network structure, which exhibits a large specific surface and excellent electrical conductivity, thus guaranteeing sufficient, stable, and efficient oxygen reduction reaction (ORR)/OER active sites. Therefore, the N2 ‐NiFe‐PBA/NCF/CC‐60 electrode delivers high‐efficiency OER activity with a low overpotential (270 mV at 50 mA cm −2 ) and excellent ORR performance with a positive potential of 0.89 V at 5 mA cm −2 . The N2 ‐NiFe‐PBA/NCF/CC‐60 based Zn–air batteries display outstanding discharge/charge stability for 2000 cycles. Meanwhile, the corresponding flexible Zn–air batteries with satisfactory mechanical properties exhibit a low voltage gap of 0.52 V at 1.0 mA cm −2 . Abstract : A flexible free‐standing bifunctional electrode (N2 ‐NiFe‐PBA/NCF/CC‐60) is constructed by the 3D spatial combination of CN vacancy‐mediated NiFe‐PBA and N‐doped carbon nanofibers rooted on carbon cloth. The N2 ‐NiFe‐PBA/NCF/CC‐60 electrode delivers high‐efficiency and stabilized bifunctional oxygen reduction and oxygen evolution reaction catalytic performance. Furthermore, the N2 ‐NiFe‐PBA/NCF/CC‐60 based Zn–air battery operates 2000 discharge/charge cycles.